Krishna
0

Step 1: Rewrite the problem using the same base. 

EXAMPLE: 3^x\ =\ 9^{\left(y-1\right)}

                   3^x\ =\ \left(3\cdot3\right)^{y-1}

                  3^{x\ }\ =\ 3^{2\left(y-1\right)}


Step 2: Use the laws of exponents  to simplify the equation

NOTE: Since the bases are the same, we can drop the bases and set the exponents equal to each other.

EXAMPLE: 3^{x\ }\ =\ 3^{2\left(y-1\right)}

                     x\ =\ 2\left(y-1\right)


Step 3: Simplify the equation and verify, is it showing the given equation or not